Book Review: Islamic Jurisprudence – An International Perspective - Hussain, S. Jaffer (Journal of Malaysian and Comparative Law, 2019)
Book Review of Islamic Jurisprudence – An International Perspective authored by Professor C.G. Weeramantry.